The Impact of Remittances on Economic Growth in a Remittance Receiving Country - Hossain, Md. Shahadat; Chin, Lee; Said, Rusmawati; Ishak, Suryati (Advances in Social Sciences Research Journal, 2025)
The study is to examine the impact of remittances on economic growth, in particular how the development of domestic financial sector influences a country’s capacity to take advantage of remittances. Bangladesh’s remittances, specifically inflows, are an important source of income support and economic growth. Employing ARDL model on a dataset of 46 years from 1976 to 2021, this study finds that remittances boost growth in Bangladesh with developed financial systems. The study also finds that capital formation is positively associated with economic growth in the long run while remittance is negatively influencing economic growth. Thus, policies should focus on developing the financial system, reducing the cost of remitting and encouraging migrants to send remittances using formal channels.